A Novel Calix[4]Crown-Based 1,3,4-Oxadiazole as a Fluorescent Chemosensor for Copper(II) Ion Detection - Sun, Chun; Du, Siyi; Zhang, Tianze; Han, Jie (Frontiers in Chemistry, 2021)
The synthesis and characterization of a novel florescent chemosensor 1 with two different types of cationic binding sites has been reported in this work, which is a calix[4]crown derivative in 1,3-alternate conformation bearing two 2-phenyl-5-(4-dimethylaminopyenyl)-1,3,4-oxadiazole units. The recognition behaviors of 1 in dichloromethane/acetonitrile solution to alkali metal ions (Na+, K+), alkaline earth metal ions (Mg2+, Ca2+) and transition metal ions (Co2+, Ni2+, Zn2+, Cd2+, Cu2+, Mn2+, Ag+) have been investigated by UV-Vis and fluorescence spectra. The fluorescence of 1 might be quenched selectively by Cu2+ due to the photo-induced electron transfer mechanism, and the quenched emission from 1 could be partly revived by the addition of Ca2+ or Mg2+, thus the receptor 1 might be worked as an on-off switchable fluorescent chemosensor triggered by metal ion exchange.